1
$\begingroup$

My book gives this Lagrangian:

$$ L = -|\partial \phi|^2 -V(\phi) -\bar \psi_L \not \partial \psi_L -\bar \psi_R \not \partial \psi_R -g(\phi \bar \psi_L \psi_R + \phi^* \bar \psi_R \psi_L) $$

It's supposed to have $U(1)$ symmetry, with $\phi$ having charge $+1$, $\psi_L$ having $+1/2$ and $\psi_R$ having $-1/2$, which is the reason for those cubic terms.

However, the book also says that

$$ \psi_{L/R} = \frac{1}{2}(1\pm\gamma_5)\psi $$

so I deduce that

$$ \bar \psi_L \psi_R = \frac{1}{4} \bar \psi (1+\gamma_5)(1-\gamma_5)\psi = \frac{1}{4}\bar \psi (1-\gamma_5^2)\psi = 0 $$

because $\gamma_5^\dagger = \gamma_5$ and $\gamma_5^2 = 1$.

It's can't be zero otherwise the interaction terms given by the book are wrong. What happened?

EDIT:

$$ \bar \psi_L = \psi_L^\dagger \gamma_0 = \frac{1}{2}\psi^\dagger (1+\gamma_5)\gamma_0 = \frac{1}{2}\psi^\dagger \gamma_0 \gamma^0 (1+\gamma_5)\gamma_0 = \frac{1}{2}\bar \psi (1+\gamma_5) $$

using $\gamma_0 \gamma^0 = 1$ and $\gamma^0 \gamma_5 \gamma_0=\gamma_5$.

$\endgroup$
3
  • 2
    $\begingroup$ I think you need to flip the sign of the $\gamma_5$ when you move it past a $\gamma_0$ $\endgroup$
    – Ihle
    Commented May 24, 2015 at 19:51
  • $\begingroup$ @Ihle I edited the post to explain how I calculated the Dirac adjoint. $\endgroup$
    – Lelota
    Commented May 24, 2015 at 20:00
  • $\begingroup$ @Lelota look again at what you typed. It is clear that you imagined one more $\gamma^0$ that wasn't there. $\endgroup$
    – Danu
    Commented May 25, 2015 at 9:26

3 Answers 3

2
$\begingroup$

@Ihle is right. $\gamma^5\gamma^0=-\gamma^0\gamma^5$. You don't need to insert $\gamma^0\gamma^0$.

$\endgroup$
2
$\begingroup$

Your second last step is incorrect: $\bar{\psi}_L = \frac{1}{2}\psi^\dagger\gamma_0\gamma^0(1+\gamma_5)\gamma_0 = \frac{1}{2}\bar{\psi}(1-\gamma_5)$, since $\{\gamma_5,\gamma_\mu\} = 0 \implies \gamma_5\gamma_0 = -\gamma_0\gamma_5$.

$\endgroup$
1
$\begingroup$

$$\overline{\psi_L}\psi_R = \overline{\frac{1}{2}(1-\gamma^5) \psi} \frac{1}{2}(1+\gamma^5)\psi=\left(\frac{1}{2}(1-\gamma^5) \psi\right)^\dagger \gamma^0 \frac{1}{2}(1+\gamma^5)\psi = \psi^\dagger\frac{1}{2}(1-\gamma^5)\gamma^0\frac{1}{2}(1+\gamma^5)\psi$$ Since $\gamma^5\gamma^0 = -\gamma^0 \gamma^5$, it yields: $$\overline{\psi_L}\psi_R = \psi^\dagger \gamma^0 \frac{1}{2}(1+\gamma^5) \frac{1}{2}(1+\gamma^5)\psi = \overline{\psi}\frac{1}{2}(1+\gamma^5)\psi \ne 0 $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.